Racial Justice and Racialized Religion: Are Progressive White Christians Getting It Right? - Marti, Gerardo (Sociology of religion, 2024)
The core question guiding this research is: What happens when the project of racial justice, specifically, anti-black racism, is taken on by white progressive Christians and their churches? Acknowledging religion as racialized allows our scholarship to be more discerning and less naive, especially regarding the true potential of racial justice—even among those who are most faithfully attempting to become antiracist. Drawing from preliminary data collected from congregations in the United States and Canada aligned with the Alliance of Baptists, a denomination explicitly committed to antiracism, I focus on a few significant dynamics, briefly summarized under seven themes: (1) Getting It Right, (2) The Volunteer Antiracist, (3) Congregational Politics, (4) Encountering Resistance, (5) Soliciting Cooperation, (6) Instrumentalizing Whiteness as a Ready Tool, and (7) Affirmation from Black Members. As data collection continues, this research remains open to developing more insights and revising tentative conclusions as the analysis proceeds further.